The influence of work motivation and self management practices on employee job satisfaction (case study of pt. Bio farma in Bandung) - Tarmidi, Didi; Yusup, Aditya Muhammad (Technium Sustainability, 2021)
This research aims to determine how the description of work motivation, self-management practices, and employee job satisfaction, as well as to determine how the influence of work motivation and self-management practices on employee job satisfaction PT. Bio Farma. The factors tested in the study were work motivation and self-management practices as independent variables, while job satisfaction was dependent variables. The research methods used in this research are descriptive and verification methods. The population in this study were employees at PT. Bio Farma. The sampling technique used in this study was Purposive Sampling and the size of the sample in this study was calculated with the formula Slovin, so the total number was 200 respondents. The analytical methods used in this study are some linear regression analyses using SPSS25 for Windows. The results of this study show that work motivation and self-management practices affect employee job satisfaction at PT. Bio Farma. The effect of work motivation and self-management practices on employee job satisfaction was 59.3%.